HUBUNGAN PENGETAHUAN DAN STATUS EKONOMI DENGAN STATUS GIZI IBU HAMIL - Rachmah, Siti; Yudha Laga hadi Kusuma; Wulandari (MEDICA MAJAPAHIT, 2022)
ABSTRACT Nutrition of pregnant women greatly determines their health and their content. The food consumed by pregnant women is useful for facilitating birth and for the production of breast milk for the baby. Lack of knowledge and low economic status causes the nutritional needs of pregnant women to be unfulfilled, resulting in SEZ. This study aims to determine the relationship between knowledge and economic status with nutritional status in pregnant women. Analytical survey research design with a cross sectional approach. The independent variables are knowledge and economic status, the dependent variable is the nutritional status of pregnant women. The population is all pregnant women at the Mojosari Health Center, totaling 33 pregnant women, with a simple random sampling technique obtained 30 respondents. Data analysis used the Spearman Rank test. The results of statistical tests that the value of count = 0.000 table = 0.01, The results of statistical tests obtained count = 0.002 table = 0.01. Based on the correlation coefficient, it was found that the value of C = 0.533 had a moderate level of closeness. The better the knowledge, the easier it is to receive information and the more knowledge they have, as well as the knowledge of pregnant women will affect daily consumption patterns which have an impact on nutritional status. Families with high economic status will certainly try to meet the needs of pregnant women as well as possible, quality and diverse nutritional intake can support the nutritional status of pregnant women. ABSTRAK Nutrisi ibu hamil sangat menentukan kesehatan dan kandungannya. Makanan yang dikonsumsi ibu hamil berguna untuk memperlancar persalinan dan untuk produksi ASI bagi bayi. Kurangnya pengetahuan dan status ekonomi yang rendah menyebabkan kebutuhan gizi ibu hamil tidak terpenuhi sehingga terjadi KEK. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan dan status ekonomi dengan status gizi pada ibu hamil. Desain penelitian survey analitik dengan pendekatan cross sectional. Variabel bebas adalah pengetahuan dan status ekonomi, variabel terikat adalah status gizi ibu hamil. Populasi adalah seluruh ibu hamil di Puskesmas Mojosari yang berjumlah 33 ibu hamil, dengan teknik simple random sampling diperoleh 30 responden. Analisis data menggunakan uji Rank Spearman. Hasil uji statistik bahwa nilai hitung = 0,000 tabel = 0,01, Hasil uji statistik diperoleh hitung = 0,002 tabel = 0,01. Berdasarkan koefisien korelasi diketahui bahwa nilai C = 0,533 memiliki tingkat keeratan sedang. Semakin baik pengetahuan maka semakin mudah menerima informasi dan semakin banyak pengetahuan yang dimilikinya, begitu juga dengan pengetahuan ibu hamil akan mempengaruhi pola konsumsi sehari-hari yang berdampak pada status gizi. Keluarga dengan status ekonomi tinggi tentunya akan berusaha memenuhi kebutuhan ibu hamil dengan sebaik-baiknya, asupan gizi yang berkualitas dan beragam dapat menunjang status gizi ibu hamil.